The Effect of Exercises and Gender on Cardiorespiratory Endurance in the Elderly - Prabowo, Arif; Sulaiman, Sulaiman; Soenyoto, Tommy (Journal of Physical Education and Sports, 2019)
One of the appropriate sports for the elderly is elderly exercises. The exercises require low-impact movement but still can stimulate heart-lungs work, so it is suitable for the condition of the elderly. This study aims to analyze the effect of exercises and gender on cardiorespiratory endurance. This experimental research employed a 2x2 factorial design. There were 20 older adults from Keluarga Harapan Program selected as the sample, and the technique of data collection was purposive sampling. Subsequently, the sample was divided into four experimental groups. The technique of data analysis employed Two Way Anova. The results of the study are, first: Sang Surya and Lansia Bugar exercises affect the cardiorespiratory endurance (Fvalue = 17.308 > Ftable = 3.59). Lansia Bugar exercise is better than Sang Surya exercise. Secondly, there is an effect of gender between male and female on the cardiorespiratory endurance (Fvalue = 56.077 > Ftable = 3.59). Male older adults affected cardiorespiratory endurance more than the female. Thirdly, there is an interaction of exercises and gender on the cardiorespiratory endurance (Fvalue = 22.231 > Ftable = 3.59). The conclusion of this study is exercises and gender affect cardiorespiratory endurance so that they can maintain the health and fitness of older adults.